Information for contributors and readers for issue 3-2018 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2018)
On 2 May 2018, the Committee on Publication Ethics (COPE) approved a membership of the Military Technical Courier in its organization. COPE provides leadership in thinking on publication ethics, practical resources to educate and support members, and offers a professional voice in current debates.